Inmunoterapia con alérgenos, ¿cuándo y por qué? (2015)
ABSTRACT: Allergen specific immunotherapy is currently the only treatment that modifies the natural course of allergic diseases. Its present indications are asthma, rhinitis, conjunctivitis, atopic dermatitis and hymenoptera venom allergy. However, there still is some controversy regarding its safety and clinical utility. In this article, we present a review about the molecular mechanisms, indications, contraindications, safety and efficacy of immunotherapy in each one of these diseases, by means of illustrative cases. Key words: Allergens; Allergy; Asthma; Atopy; Conjunctivitis; Dermatitis; Hymenoptera; Immunotherapy; Rhinitis; Sensitization.